The Gap between Urban and Rural Development Levels Narrowed. (28th September 2020) - Wang, Mou; Kang, Wenmei; Zhang, Ruiying
Abstract : The difference between urban and rural development levels (URDL) and the deficiency of rural development level have become the weak points for China to achieve balanced and high-quality development. In order to reveal the changing trend of urban-rural differences in China over the years and provide a reference for the policy-making of the balanced development of urban and rural areas and high-quality economic development, this paper uses the United Nations Development Program-adjusted Human Development Index (HDI) calculation method to calculate the urban and rural areas, based on 1995–2017 national time series data and provincial panel data. On this basis, this paper uses the Logarithmic Mean Weight Divisia to decompose the dynamic changes of the difference of URDL and analyzes the spatial equilibrium of the change trend of the differences of URDL, supplementing the shortcomings of the existing literature which only focuses on income, education, and other local areas and lacks continuity and comparison. The research finds that 1. based on the time series analysis of the difference of URDL, this paper firstly proposes the "inverted U" curve for the difference of URDL in China, which shows that the difference of URDL in China has experienced a process from expansion (1995–2001) to high fluctuation (2001–2011) to continuous convergence (2011–2017). 2. From the factor decomposition effect of the difference of URDL, the difference expansion period is caused by the increase in the gap between the Health Index, the Education Index, and the Income Index. With the decline in the gap between education levels and life expectancy, the growth trend of China's urban-rural gap has been suppressed, and it has entered a high platform period with relative small fluctuation. After 2011, benefiting from the large decline in income level gaps, China's urban-rural difference has entered a period of convergence. 3. From the perspective of the spatial evolution characteristics of the gap of URDL, the overall coefficient of variation of the country has shown a downward trend. The degree of spatial equilibrium is gradually increasing, and the overall changes in the east, west, and northeast are the same as the overall trend of the country. The decline in the northeast is the largest, the west is the second, and the east is the least. The middle shows a slight upward trend, but the value of each year is always smaller compared with other regions. Generally speaking, the gap of URDL is relatively good in the middle and northeast, followed by the east, and there is still much room for improvement in the balance of the west.